Pengaruh Promosi, Harga, Kualitas Produk, dan Kualitas Pelayanan terhadap Kepuasan Pelanggan: Studi pada PT Jaringan Fiber Nusantara Jombang - Devita Agustina; Machin Machin; Evan Andrianto Ammaridho (Yayasan Literasi Sains Indonesia, 2025)
The primary objective of this study was to analyze the extent to which WiFi users of PT Jaringan Fiber Nusantara Jombang are satisfied and the determinants behind it by promotion, price, product quality, and service quality. This study involved Wi-Fi customers of PT Jaringan Fiber Nusantara Jombang and used quantitative methods of multiple linear regression analysis. A total of 89 individuals provided responses to the questionnaire, which served as the primary source of data. In conducting the analysis, T-test, F-test, and coefficient of determination (R²) were implemented. The results of hypothesis testing show that promotion (X1) (sig. 0.029; t = 2.215 > 1.663), product quality (X3) (sig. 0.012; t = 2.577 > 1.663), and service quality (X4) (sig. 0.000; t = 6.332 > 1.663 demonstrate a meaningful and favorable impact on customer satisfaction. Meanwhile, price (X2) (sig. 0.516; t = -0.652 < 1.663) has no significant effect on customer satisfaction. The results showed that X1, X3, X4 have a positive and significant effect on customer satisfaction, while X2 has no significant effect. This finding indicates that customers prioritise promotion, product quality, and service quality over price. It is expected that the results of the study will provide guidance for the company in improving promotional strategies, maintain product quality, improve service, and build customer loyalty to support business sustainability.